Tendon et acide hyaluronique - Kaux, J. F.; Samson, A.; Crielaard, J. M. (Science & Sports, 2015)
Objectives: This review analyses studies (in vitro, in vivo in animals and in humans) relative to the use of hyaluronic acid in the treatment of tendinopathies. News: Recently, properties of the visco-elasticity on liquid connective tissue of hyaluronic acid are proposed in the treatment of tendinopathies. Fundamental studies show encouraging results with regard to the ability of the hyaluronic acid to promote tendon slipping and limited adhesion as well as to make better tendinous architectural organization. These observations appear to be supported by encouraging clinical results on pain and function. Prospects and projects: This literature review identifies studies investigating the effect of hyaluronic acid on tendons. In total, 17 articles to the hyaluronic acid applied tendons were selected for their relevance and scientific quality, including 7 for the part in vitro, part 4 in vivo animal and 6 for human. These items will be the basis of a critical analysis of this recent indication of this treatment. Conclusion: Controlled randomized studies are still necessary to clearly demonstrate the effectiveness of hyaluronic acid for treating tendinopathies.